RipetaScore: Measuring the Quality, Transparency, and Trustworthiness of a Scientific Work - Sumner, Josh Q.; Vitale, Cynthia Hudson; McIntosh, Leslie D. (Frontiers in Research Metrics and Analytics, 2022)
A wide array of existing metrics quantifies a scientific paper’s prominence or the author’s prestige. Many who use these metrics make assumptions that higher citation counts or more public attention must indicate more reliable, better quality science. While current metrics offer valuable insight into scientific publications, they are an inadequate proxy for measuring the quality, transparency, and trustworthiness of published research. Three essential elements to establishing trust in a work include: trust in the paper, trust in the author, and trust in the data. To address these elements in a systematic and automated way, we propose the ripetaScore as a direct measurement of a paper’s research practices, professionalism, and reproducibility. Using a sample of our current corpus of academic papers, we demonstrate the ripetaScore’s efficacy in determining the quality, transparency, and trustworthiness of an academic work. In this paper we aim to provide a metric to evaluate scientific reporting quality in terms of transparency and trustworthiness of the research, professionalism, and reproducibility.